Progressive-toric IOL design reduces residual astigmatism with increasing pupil size: a ray-tracing simulation based on corneal topography data - Łabuz, Grzegorz; Vàradi, Dorottya; Khoramnia, Ramin; Auffarth, Gerd U. (Biomedical optics express, 2021)
Population studies indicate that astigmatism decreases from the corneal center toward the periphery. A standard toric intraocular lens (IOL) with a constant cylinder power cannot correct uniformly across this gradient. We built an astigmatic eye model based on corneal topography data. A progressive-toric lens with gradually decreasing cylinder power was compared with an identically designed lens but featuring conventional astigmatism correction. Residual astigmatism did not differ significantly (P=0.06) at 3 mm, and the Strehl ratio was identical for both lenses (0.51 ±0.15, P=0.88). At 5 mm, the progressive IOL yielded significantly lower residual astigmatism by 0.10 D (P<0.001). The Strehl ratio was 0.30 ±0.08 with the progressive and 0.29 ±0.08 with the standard lens (P<0.001). At 3 mm, the optical performance was comparable for both IOLs. However, at 5 mm, the progressive-toric was more effective in correcting astigmatism, and it yielded reduced residual astigmatism compared to a standard toric lens.
Gesehen am 21.05.2021